Pengendalian Resiko Kecelakaan Kerja dengan Metode Job Safety Analysis pada Pekerja Pemanen Kelapa Sawit PT. Mitra Unggul Pusaka Kebun Segati - Wiranata, Rendi; Nasirly, Riri; Nurjanah, Siti (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2024)
Job Safety Analysis method is a safety management technique that focuses on identifying hazards and controlling hazards related to the series of work or tasks to be carried out. One of the causes of work accidents is due to worker negligence while working. This literature review was carried out using the traditional literature review method. Article sources were obtained from the Google Scholar database and the Garuda Portal, with a year range from 2018 – 2022. The keywords used are 'work accident and job safety analysis articles' and 'work accidents and job safety analysis'. The research results show that the cause of work accidents that often occur is the use of personal protective equipment (PPE). Apart from that, there are human factors such as unsafe actions and still lack of knowledge about work safety. The research results also show that every job has a risk of accidents, so you should always prioritize safety and focus on doing the job.